2020
DOI: 10.3390/buildings10040079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on Embodied Energy of Non-Load Bearing Walls for Office Buildings

Abstract: Two important factors that have been put in the limelight in the current age are environmental concerns and sustainable future. The building sector has emerged as an important player in this matter due to their contribution into the large share of resources and energy consumption as well as harmful greenhouse gas emission. This paper discusses the percentage of embodied energy (EE) in two common building wall materials in Malaysia: steel and concrete. Concrete is used in concrete non-load bearing walls and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…The life cycle of a building can be divided into three main stages: production, construction, and use and demolition [56][57][58][59]. The scope of the LCA's evaluation is, therefore, divided into "Cradle to Gate", "Cradle to Gate with Option", and "Cradle to Grave" [60][61][62]. "Cradle to Gate" assesses only the material production stage, and "Cradle to Grave" covers the entire life cycle of a building from the material production stage to the dismantling and disposal stage [63][64][65].…”
Section: Compares Thmentioning
confidence: 99%
“…The life cycle of a building can be divided into three main stages: production, construction, and use and demolition [56][57][58][59]. The scope of the LCA's evaluation is, therefore, divided into "Cradle to Gate", "Cradle to Gate with Option", and "Cradle to Grave" [60][61][62]. "Cradle to Gate" assesses only the material production stage, and "Cradle to Grave" covers the entire life cycle of a building from the material production stage to the dismantling and disposal stage [63][64][65].…”
Section: Compares Thmentioning
confidence: 99%
“…The environmental impact of OE use is a well-established area of research and practice, with well-defined metrics, methodologies, building codes and regulations (Hu, 2020). Different authors argue that the better energy performance and efficiencies of the buildings have decreased the role of operating energy in a building's life cycle, compared to the EE, which plays an increasing role (Dixit et al , 2012; Dixit, 2019; Salehian et al , 2020). Under Dixit (2019), optimizing operating energy is also easier and more streamlined than EE because of the complexity of EE calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors highlight the importance of the exterior wall and the structural system in the total amount of EE and CO 2 emissions (Salehian et al , 2020; Hu, 2020; Sposto and Paulsen, 2012 and Paulsen and Sposto, 2013). In a case study conducted in a Brazilian social housing project constructed with structural ceramic block masonry, it was found that almost 60% of the EE resulted from the materials used to build the walls (Sposto and Paulsen, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation